Pengaruh Puzzle Terhadap Peningkatan Perkembangan Motorik Halus Anak Prasekolah Di Tk Santo Yoseph Denpasar - Ni Kadek Dian Arisanti; Anak Ayu Nyoman Trisna Narta Dewi; Agung Wiwiek Indrayani (Direktorat Politeknik Kesehatan Makassar, 2024)
Various things can affect motor development in early childhood, both internal and external factors. Stimulation in the form of puzzles is one of the factors that increase children's fine motor development. The purpose of this study is to prove the effect of offering jigsaw puzzles to improve fine motor development in preschool children. The research method used was experimental with intervention and control groups and using simple random sampling technique with a total of 25 samples. The intervention group consists of 13 children who are given puzzles and the control group, consisting of 12 children, are given freedom to play other games such as playing in the field. The results showed an increase in fine motor development in preschool children at Tk Santo Yoseph Denpasar after being given a puzzle, as evidenced by the Wilcoxon Test results of 0.005 (p<0.05) in the intervention group during the pre- and post-test and the results of the Mann-Whitney Test posttest data of 0.021 (p<0.05). Based on the research that has been conducted, it can be concluded that there is an effect of offering puzzles on children's fine motor development and changes in the level of children's fine motor development in the intervention group after they have been given puzzles.